Dynamic Interaction of Bridge Spans and Piers as a Tuned System for Seismic Load Reduction - Ziyovuddin Rahimjonov; Fakhriddin Zokirov; Lintang Dian Artanti (Journal of Global Engineering Research and Science, 2026)
Bridges located in seismic regions are subjected to significant dynamic loads that may cause considerable forces in bridge piers and foundations. Traditional seismic design methods usually consider the span structure as a rigid mass transferring inertial forces to the supports. However, this approach does not account for the potential dynamic interaction between the span and the supporting structure. This study proposes a method for reducing seismic forces in bridge piers by using the span structure as a tuned dynamic system. In the proposed approach, the bridge span is considered as a dynamic vibration absorber interacting with the pier. A mathematical model based on a two-degree-of-freedom system is developed to describe the dynamic behavior of the bridge–pier system under seismic excitation. Parametric analysis is carried out to determine the optimal stiffness and damping parameters that minimize seismic forces in the pier. The results show that appropriate tuning of the span structure significantly reduces dynamic responses. In particular, the bending moment in the bridge pier can be reduced by up to 2.3 times compared with traditional seismic design approaches. The proposed method can be applied in seismic regions for improving the seismic performance and reliability of bridge structures.